The insistence of a weak God. Philosophical approaches to the notion of event in the work of John D. Caputo - Rubín Álvarez, Abraham (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
The work of the North American philosopher and theologian John D. Caputo revolves around the attempt to transfer certain approaches of postmodern philosophy to the field of religion and the theme of the divine. In this sense, he recovers the notion of weakness, famous in the work of Gianni Vattimo, and puts it to work at the same time with some of the motifs that have become particularly well known since Jacques Derrida. Some examples are l’avenir (to come), spectres or the priority of the other. All of them are indebted to the notion of event, from which Caputo proposes a new way of understanding divinity, more in line with postmodern philosophy and, especially, deconstruction.
Keywords: God; weakness; event; Caputo; Derrida; Vattimo